Seasonal near-surface hypoxia in a temperate fjord in Clayoquot Sound, British Columbia - Rosen, Sarah; Bianucci, Laura; Jackson, Jennifer M.; Hare, Alex; Greengrove, Cheryl; Monks, Rowen; Bartlett, Mackenzie; Dick, Jared (Frontiers in Marine Science, 2022)
While fjords often have low oxygen concentrations in their deep waters, this research identified seasonal, near-surface hypoxia (≤ 2 mL L-1 or 2.9 mg L-1) through a year-long monthly time series in Clayoquot Sound, British Columbia. Temperature, salinity, and oxygen data were collected monthly in the upper 50 m at three stations in Herbert Inlet from June 2020 to July 2021, marking the first time series of its kind in a Clayoquot Sound fjord. Hypoxic conditions were shallowest (minimum depth of 12 m) and most intensified in summer; near-surface hypoxia was recorded at one or more stations in all months except in winter. Considering that many local marine species, including wild Pacific salmon, experience adverse effects at oxygen concentrations much higher than the hypoxic threshold, we note that 50 to 100% of the upper 50 m of Herbert Inlet consistently presented low oxygen concentrations (defined here as a guideline as ≤ 4.9 mL L-1 or 6.9 mg L-1) during the 14-month study period. Previous observations collected sporadically since May 1959 confirmed the presence of hypoxic conditions in the past. These findings suggest that long-term, multidisciplinary studies are needed to understand and predict the impact of hypoxia and deoxygenation on wild salmon stocks as climate changes.